Physical activity and BMI inequalities throughout childhood: a Brazilian birth cohort studyResearch in context - Shelby A. Keye; Pedro Curi Hallal; Inacio Crochemore-Silva; Marlos Rodrigues Domingues; Giulia Salaberry Leite; Otávio Amaral de Andrade Leão (The Lancet Regional Health. Americas)
Summary: Background: Utilising the 2015 Pelotas (Brazil) Birth Cohort, the current study investigated differences in physical activity (PA) and BMI-for-age between sex, race, and socioeconomic status (SES) at ages 1 (n = 4018), 2 (n = 4014), 4 (n = 4010), and 7 (n = 3867). Methods: Demographics collected via surveys included sex at birth, skin colour, a proxy for race, at 4 years, and an assets index collected at all ages to determine SES. Height and weight estimated BMI-for-age and PA via wrist-worn accelerometers. Means and 95% confidence intervals described PA and BMI-for-age, using t-tests, ANOVAs, and chi-squared tests to determine significant differences. Trajectory models compared longitudinal patterns from 1 to 7 years. Findings: Starting at age 2, Black and Brown children and poorer children engaged in more PA. Poorer children presented lower BMI-for-age at ages 4 and 7. Trajectory models revealed that boys, Black and Brown, and poorer children represented increasing and high PA groups. Boys and Black and Brown children were most prevalent in higher BMI-for-age trajectory groups. Interpretation: The current study revealed PA and BMI-for-age inequalities across multiple demographic variables during early life. These results may reveal when inequalities may arise and reveal time points to intervene for populations at risk of poor health-related quality of life. Funding: The present study was funded initially by the Wellcome Trust (095582), and partially by the Conselho Nacional de Desenvolvimento Científico e Tecnológico, Fundacao de Amparo a Pesquisa do Estado do Rio Grande do Sul, Children’s Pastorate, and the Department of Science and Technology (DECIT/Brazilian Ministry of Health).